2018
DOI: 10.1016/j.jeurceramsoc.2017.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Tough salami-inspired Cf/ZrB2 UHTCMCs produced by electrophoretic deposition

Abstract: One of the biggest challenges of the materials science is the mutual exclusion of strength and toughness. This issue was minimized by mimicking the natural structural materials. To date, few efforts were done regarding materials that should be used in harsh environments. In this work we present novel continuous carbon fiber reinforced ultra-high-temperature ceramic matrix composites (UHTCMCs) for aerospace featuring optimized fiber/matrix interfaces and fibers distribution. The microstructures-produced by elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Refractory compounds of transitional metals (Ta, Nb, Ti, Zr, Hf) usually serve as the basis for UHTCs [5]. Potential applications of UHTCs include hightemperature solar concentrators for renewable energy industry, barrier coatings, hard coatings [6][7][8][9]. TaC (Tm=3950°С) and ZrC (Tm=3420 °С) are among the most refractory compounds known today [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Refractory compounds of transitional metals (Ta, Nb, Ti, Zr, Hf) usually serve as the basis for UHTCs [5]. Potential applications of UHTCs include hightemperature solar concentrators for renewable energy industry, barrier coatings, hard coatings [6][7][8][9]. TaC (Tm=3950°С) and ZrC (Tm=3420 °С) are among the most refractory compounds known today [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…1) The continuous fibrous reinforcement is coated with interphase layers, typically pyrolytic carbon [276] or ceramic [275], [277] to enhance the fracture toughness of the composite and protect the fibres during pressing.…”
Section: Sintering Approaches Hp Sps Hip and Pressurelessmentioning
confidence: 99%
“…However, as discussed by Zoli et al [281], despite the formation of brittle phases, pull-out still occurs because of the onion-like structure of the carbon fibres. It has also been reported that other mechanisms of toughening are activated, either crack deflection [275] or, in weak matrix composites such as porous Cf-ZrB2 [279] , with a fracture mechanism similar to that which occurs in oxide-oxide CMCs [282]. Table 9 [275], [276], [278], [279], [281], [283] summarises the thermomechanical behaviour achieved by hot pressed UHTCMCs, including microstructural and physical properties.…”
Section: Sintering Approaches Hp Sps Hip and Pressurelessmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the precursors used, the composition of the infiltrated samples varied in the amount of ZrC and ZrB 2 [25]. Finally, both SiC f and C f /ZrB 2 UHTCMCs, coupling conventional impregnation techniques with sintering by hot pressing were recently fabricated [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%